2012
DOI: 10.1089/ast.2011.0805
|View full text |Cite
|
Sign up to set email alerts
|

Planning for Mars Returned Sample Science: Final Report of the MSR End-to-End International Science Analysis Group (E2E-iSAG)

Abstract: 3.4. The importance of rock and soil sample suites 4. Achieving the Proposed Scientific Objectives-Samples Required/Desired 4.1. Integrated priorities for rock samples 4.1.1. Considerations in designing the suites of rock samples 4.1.2. Possible/probable variations in rock we need to be prepared to detect and sample 4.1.3. Scientific value of a subsurface rock sample 4.1.4. Number of rock samples desired/required 4.2. Considerations related to the number and type of regolith samples 4.2.2. Regolith-sampling im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 204 publications
(244 reference statements)
0
12
0
Order By: Relevance
“…Figure 4 illustrates an example application of the triage operation on a subset of the samples used in this study, where resource limitations require that candidate samples are eliminated at each phase. In analogy to a Mars sample return mission, the priority would be to detect evidence of past or present life (McLennan et al, 2012 ). To this end, the correctness of the sample ranking process was evident during the very first triage step using single-step pyrolysis-FTIR at 1000°C where the highest-priority samples were correctly ranked ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 4 illustrates an example application of the triage operation on a subset of the samples used in this study, where resource limitations require that candidate samples are eliminated at each phase. In analogy to a Mars sample return mission, the priority would be to detect evidence of past or present life (McLennan et al, 2012 ). To this end, the correctness of the sample ranking process was evident during the very first triage step using single-step pyrolysis-FTIR at 1000°C where the highest-priority samples were correctly ranked ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…A ttempts to discover whether life exists or has previously existed on Mars have not yet been conclusive. To seek greater certainty when reading the rock record of habitability and habitation on Mars, mission concepts are being proposed that involve the return of samples to Earth (McLennan et al, 2012 ). Once on Earth, samples of Mars can be distributed to multiple laboratories that host the most powerful analytical techniques available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of them come from orbiters; some come from landers and rovers. They contain various geological units and structures from sedimentary, volcanic, tectonic, and impact origin gathered from the United States Geological Survey maps of Mars (Tanaka et al, 2005(Tanaka et al, , 2014, the NASA/International Cartographic Association (ICA) Integrated Database of Planetary Features (Hargitai, 2016; more information on the data and their authors can be found at planetarydatabase.wordpress.com), the NASA Mars Crater Database (Robbins & Hynek, 2012), and individual sources (Bleacher et al, 2007(Bleacher et al, , 2009Carter et al, 2013;Dohm et al, 2000;Ehlmann & Edwards, 2014;Farmer, 1996;Hauber et al, 2013;Hynek et al, 2010;Irwin & Grant, 2009;Malin & Edgett, 2000;Malin et al, 2010;Marzo et al, 2010;Metz et al, 2009;Osterloo et al, 2010;Richardson et al, 2013). Among these sites, the geological units do not necessarily contain any interesting targets, because some correspond to a mixture of undifferentiated rocks at the considered resolution and others stand in dusty areas.…”
Section: Data Types and Sourcesmentioning
confidence: 99%
“…A future Mars Sample Return (MSR) mission would aim to utilize the unrestricted investigative potential of Earth-based instrument suites to provide further insight into the question of martian life (McLennan et al , 2012). The requirements of the MSR in situ mission phase would differ from those on previous Mars missions.…”
Section: Introductionmentioning
confidence: 99%